Travelers' motivations to adopt augmented reality (AR) applications in a tourism destination. (28th May 2021) - Shin, Hyejo Hailey; Jeong, Miyoung
Abstract : Purpose: This study aims to identify travelers' motivational factors to adopt augmented reality (AR) applications at tourism destinations. Furthermore, this study seeks to investigate the role of personal innovativeness as a moderator in the relationships between motivations and travelers' behavioral outcomes. Design/methodology/approach: Building upon two theories, cognitive evaluation theory and self-presentation theory, this study developed a conceptual framework to identify travelers' inclination to use AR applications at tourism destinations. A sample size of 473 was collected through an online self-administered survey. Using partial least square (PLS) analysis, the proposed model was examined. To examine the moderating effect of personal innovativeness, a multi-group analysis was conducted with two groups: high-innovative and low-innovative. PLS method is used to test the study's theoretical model. Findings: Findings of this study indicate that both hedonic and utilitarian motivations significantly influenced travelers' attitudes toward AR applications at tourism destinations. Self-presentation motivation appears to have a significantly positive impact on travelers' attitudes toward AR applications only for the highly innovative group. Originality/value: This study helps a better understanding of what motivates travelers to adopt AR applications at tourism destinations by integrating preeminent theories and applying them to the tourism context. Abstract : 论游客在旅游目的地使用AR行为 研究目的: 本论文旨在指出游客在旅游目的地使用AR的驱动因素。此外, 本论文旨在研究个人创新性在驱动因素与游客行为结果之间的调节作用。 研究设计/方法/途径: 本论文采用认知评价理论和自我表现理论作为理论基础, 建立了一个显示游客在旅游目的地使用AR应用的驱动力理论模型。本论文通过在线问卷共搜集473份数据。样本分析采用PLS分析法来验证理论模型。为了检验个人创新性的调节作用, 多组分析法在高创新性vs低创新性两组中进行。 研究结果: 研究论文结果显示享乐型价值和实用型价值都对游客在旅游目的地使用AR的态度有显著作用。自我表现激励因素只对高创新性游客组对AR态度有着显著作用。 研究原创性/价值: 本论文通过整合理论, 将其应用到旅游情境中, 解释了游客为何在旅游目的地使用AR的行为。